Sustainable education for the XXI Century: Prospects of developing countries towards innovation of the educational model - Hernández Estrada, Guzmán (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
The proposal aims bring a sustainable educational model responding to the needs of developing countries in terms of economy, society, environment and culture media having as basic principle the analysis of different effects by analyzing the prospects of the educational models, taking as a guideline the Brundtland Report (1987) presented at the World Commission on Environment and Development United Nations and the Declaration on the sixty-ninth plenary session of UN in 2010 on culture as the fourth pillar of sustainable development. Consequently, the proposal will be to a support the indicators of the Organization for Economic Cooperation and Development (OECD) in its publications as Educationat a Glance 2014, effect a comparative analysis between developing countries.